Lymphatic Absorption of Microbial Plasmalogens in Rats - Sato, Nana; Kanehama, Aki; Kashiwagi, Akiko; Yamada, Miwa; Nishimukai, Megumi (Frontiers in Cell and Developmental Biology, 2022)
Plasmalogens, functional glycerophospholipids with biological roles in the human body, are associated with various diseases. Although a variety of saturated and/or unsaturated fatty acids in plasmalogen are presumed to have different functions in the human body, there are limited reports validating such functions of plasmalogen. In this study, we focused on bacterial plasmalogen derived from Selenomonas ruminantium subsp. lactilytica (NBRC No. 103574) with different main species of hydrocarbon chains at the sn-1 position and shorter fatty acids at the sn-2 position than animal plasmalogen. Optimum culture conditions of S. ruminantium for high-yield production of plasmalogen, such as pH and the concentration of caproic acid, were investigated under anaerobic conditions using a 2-L scale jar fermenter. The obtained plasmalogen mainly consisted of ethanolamine plasmalogen (PlsEtn). The molar ratios of PlsEtn species obtained from S. ruminantium, at sn-1/sn-2 positions, were p16:1/14:0 (68.4%), p16:1/16:1 (29.2%), p16:1/16:0 (0.7%), p16:1/15:0 (0.3%), and p17:1/14:0 (0.3%). Subsequently, duodenal infusion of the emulsion carrying the lipid extracted from S. ruminantium was carried out in lymph duct-cannulated rats. In the lymphatic plasmalogen of rats, the level of PlsEtns with molar ratios p16:1/14:0 and p16:1/16:1, the main species of plasmalogen from S. ruminantium, increased gradually until 3 to 4 h after lipid injection, and then gradually decreased. In addition, the level of PlsEtns with p16:1/20:4 and p16:1/22:6 rapidly increased, peaking at 1 to 1.5 h and 1.5 to 2 h after lipid injection, respectively. The increase in the number of PlsEtns with p16:1/20:4 and p16:1/22:6 suggested that 20:4 and 22:6, the main fatty acids at the sn-2 position in rat lymphatic plasmalogen, were preferentially re-esterified at the sn-2 position, regardless of the types of hydrocarbon chain at the sn-1 position. Thus, we showed that bacterial PlsEtns with “unnatural” structures against rats could be absorbed into the lymph. Our findings provide insights into the association between the chemical structure of plasmalogen and their biological functions in humans.